1992
DOI: 10.1148/radiology.183.1.1312736
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the pancreatic ducts: comparative evaluation with CT and MR imaging at 1.5 T.

Abstract: A prospective comparison of computed tomography (CT) and magnetic resonance (MR) imaging at 1.5 T was performed in 50 patients with the suspected diagnosis of pancreatic carcinoma. CT scans were obtained before and after administration of contrast material in 41 of 50 patients (82%); 34 of 41 postcontrast scans (83%) were obtained with dynamic CT. MR images were interpreted without knowledge of the results of CT, ultrasound, cholangiography, or endoscopic retrograde cholangiopancreatography in 48 patients (96%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(55 citation statements)
references
References 0 publications
2
49
0
4
Order By: Relevance
“…In PV invasion, the diagnostic accuracy of CT scans has been reported to be between 73 and 93% [9,10,12]. However, subtle PV invasion is difficult to detect by CT scan, and the sensitivity is reported to be between 25 and 83% [9,10,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In PV invasion, the diagnostic accuracy of CT scans has been reported to be between 73 and 93% [9,10,12]. However, subtle PV invasion is difficult to detect by CT scan, and the sensitivity is reported to be between 25 and 83% [9,10,19].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of diagnostic accuracy of arterial invasion, the CT scan was not good, ranging from 13 to 72% [9,21]. The low rate of detection of arterial invasion by CT was due to difficulties in resolving images of tortuous arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic neoplasms: While CT has been the imaging modality of choice in routine clinical evaluations of pancreatic neoplasms, newer MRI sequences have been shown to be superior in both detecting and defining local tumour extension. Studies have found the sensitivity for tumour detection to be 69% to 74% for CT and 83% to 87% for MRI (60,61). For tumours smaller than 3 cm, MRI had a sensitivity of 67%, and CT had a sensitivity of 53% (60).…”
Section: Dmentioning
confidence: 99%
“…Die MRT-Untersuchung wird noch nicht regelma Èûig fu È r die pra Èoperative Pankreasdiagnostik angewandt, da der Vorteil gegenu È ber der CT noch nicht gezeigt werden konnte. In einigen Studien konnte mittels MRT der Tumor selbst sowie dessen extrapankreatische Manifestationen (Infiltration der Duodenal-und Gefa Èû-wa Ènde) besser als mit CT dargestellt werden [24]. Der Befall von Lymphknoten galt lange Zeit als Kontraindikation fu È r eine chirurgische Intervention.…”
unclassified